(untitled) (Revista Inclusiones, 2020)
Nut production is one of the most profitable areas of agribusiness. In this study the current state of the Russian market of nut-bearing products has been assessed in the context of the dynamics of foreign economic relations and peculiarities of the global agro-industrial complex. The structure of various nuts import, peculiarities of forming prices and demand for nut-bearing products have been analyzed.